2019
DOI: 10.1002/bdr2.1550
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and pregnancy: Epigenetics and developmental origins of the metabolic syndrome

Abstract: Maternal smoking causes lower birth weight, birth defects, and other adverse pregnancy outcomes. Epidemiological evidence over the past four decades has grown stronger and the adverse outcomes attributed to maternal smoking and secondhand smoke exposure have expanded. This review presents findings of latent and persistent metabolic effects in offspring of smoking mothers like those observed in studies of maternal undernutrition during pregnancy. The phenotype of offspring of smoking mothers is like that associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 69 publications
0
91
0
3
Order By: Relevance
“…The main factors affecting fetal growth include the placenta, which guarantees the flow of nutrients to the fetus [14][15][16]. Factors causing hypoxia and reductions of blood flow in the placenta may increase the risk of FGR, SGA, and LBW [2,7]. Mechanisms of an increase or decrease in studied risk have not been univocally explained, like the processes of risk intensification in women who give up smoking in the second/third trimester.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main factors affecting fetal growth include the placenta, which guarantees the flow of nutrients to the fetus [14][15][16]. Factors causing hypoxia and reductions of blood flow in the placenta may increase the risk of FGR, SGA, and LBW [2,7]. Mechanisms of an increase or decrease in studied risk have not been univocally explained, like the processes of risk intensification in women who give up smoking in the second/third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, attention has been paid to factors impacting the fetal environment as important elements of the concept of the development of health and disease (DOHaD) [1,2]. Adverse birth outcomes have been associated not only with increased perinatal mortality and offspring neurodevelopmental disorders but also with long-term adverse health effects [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, female NIC offspring displayed higher T 3 and T 4 plasma levels; thyroids had higher TSHr and TPO protein expression, higher CAT and lower GPx activities, accompanied by higher 4-HNE, AR and ERα protein expressions. Epidemiological and experimental studies have shown that prenatal nicotine exposure induces obesity and increases the risk of diseases later in life 18 . Nicotine exposure, specifically during lactation, compromises milk yield 19 and induces adaptive changes in the offspring that lead to metabolic disorders, which include: overweight, insulin and leptin resistance and thyroid dysfunction 9,10,20 .…”
Section: Discussionmentioning
confidence: 99%